Pengukuran Dimensi Nonkontak pada Objek Bola, Silinder, dan Kubus dengan Metode Triangulasi Menggunakan Laser Garis - Gianto, Gianto (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
Dimensional measurements in the manufacturing industry are carried out to ensure that the final products are accurate in accordance with specifications. Generally, the measurement of such dimensions requires the measuring instrument to be in contact with the surface of the measuring object (contact measurement). Contact measurements may cause scratches on the measuring object. One solution to this problem is optical-based non-contact measurement using cameras. Some studies utilize reference objects in the process of converting pixels to units of length. The method requires that the reference object must always be present and appear on the image in every measurement activity. As a size standard, reference objects should not be used too often. Based on this, this study is directed to produce a non-contact measurement system with the use of reference objects only in calibration activities. This method uses the principle of laser scanner-based triangulation with an image processing method to obtain the size of the object based on the pixel coordinates of the laser beam that hits the surface of the object. The proposed system was then tested with measuring objects in the form of a ball with a diameter of 11.15 cm, a cube with a rib length of 2 cm, and a cylinder with a diameter of 8.2 cm and a height of 14 cm (based on the measurement results using a caliper). Measurements on these objects produced an average accuracy of 99.7% and an error value of 0.3%. The system can also be applied to measuring objects in the form of cylinders test weight in the field of metrology.